REFRAMING OF REAL-LIFE DISCOURSE EXPRESSIONS THROUGH METAPHORS OF PALESTINIAN KIDS: A SEMIOTIC STUDY - Saddam Hussain; Marium Majeed; Faheem Abbas; Muhammad Rashid (International Journal of Contemporary Issues in Social Sciences, 2024)
Life inside the lands of war presents the crucial aspects in which ethical and international law violations are evident. The war started between Hamas and Israel on October 7, 2022, and later, it was expanded to the whole of Palestine. Children and women have exemptions in the war, and they are given protection. War expanded, and thousands of children were killed in the war. The purpose behind the war was to genocide the children in the land. Metaphors express such meanings that cannot be presented in the official discourse. The purpose of the IDF (Israeli Defense Force) was to end the feelings of the generations against Israel. Different authors presented the lives of the children in various symbolic ways. The present study selected the three images for the analysis based on purposive sampling, such as the martyrs living to intervene and the birds and the children being transformed into angel shapes and wandering in the land of Palestine. By adopting the theoretical model of Habibova (2020) presented in the article "The Specificity of Everyday Discourses". The present study has analyzed the real-life expressions of the everyday discourse in the land of Palestine presented by the metaphorical description of the images. The study finds that the feelings and emotions are the same of the children even if they have died. At the same time, their love for land has not ended, and they keep their land closer to them than anything. The images clearly present real-life expressions. Metaphorical image construction describes both institutional and non-institutional behaviour in real life.